E-Government, Governance Quality, and Control of Corruption in ECOWAS: A Governance-System Perspective - Kerkulah P Nyeleker; Achmad Nurmandi; Chinyabuuma Bengibabuya Esther; Ruth Kunda; Herman Lawelai (Indonesian Association for Public Administration, 2026)
Corruption remains a persistent challenge to governance and sustainable development across Africa. This study examines the relationship between e-government develop- ment, governance quality, and control of corruption in the Economic Community of West African States (ECOWAS) member states. It investigates whether digital reforms can substitute for weak institutions in strengthening control of corruption or wheth- er their effectiveness depends on governance quality. A quantitative cross-sectional design was employed using secondary data from the United Nations E-Government Development Index and the Worldwide Governance Indicators for the twelve active ECOWAS countries. Descriptive statistics, Pearson correlation, and multiple regression analysis were conducted using SPSS version 17.0. The findings reveal that both e-gov- ernment development and governance quality are positively associated with control of corruption, with governance quality exhibiting the stronger institutional relationship. The results further indicate that e-government development and governance quality function as complementary components of a broader governance system rather than as competing determinants. The study advances a governance-system perspective by demonstrating that the anti-corruption potential of e-government is conditioned by governance quality. Digital reforms therefore complement, rather than substitute for, strong governance institutions in strengthening corruption control, with implications for governance reform across ECOWAS and comparable contexts.